Metastatic mediastinal malignant tumors of gastrointestinal origin with occult primary lesions: a case report - Liu, Yaxuan; Yang, Liang liang; Hu, Wen teng; Lin, Rui jiang; Bai, Song la; Ma, Min jie; Han, Biao (Frontiers in Oncology, 2025)
Cancer of unknown primary origin (CUP), accounting for 3–5% of malignancies, poses significant diagnostic challenges because of the absence of identifiable primary lesions. While common occult primary tumors involve the lung or pancreas, gastrointestinal (GI)-originated mediastinal metastases are exceedingly rare. A 54-year-old male presented with chest tightness and dyspnea. Imaging revealed a 45.5 × 36.3 mm anterior mediastinal mass. Pathological evaluation postresection revealed metastatic moderately differentiated adenocarcinoma with immunohistochemical (IHC) features (CK20+/Villin+/CK7−/TTF-1−) suggestive of GI origin. Despite comprehensive evaluations (gastroscopy, PET-CT), no primary lesions were detected. Chronic atrophic gastritis (C2) was noted, but malignancy was excluded. This case underscores the diagnostic complexity of GI-profile mediastinal CUP and highlights limitations in conventional imaging. Molecular profiling (e.g., KRAS/NRAS/BRAF mutation) and advanced diagnostics (ctDNA analysis) are critical for accurate classification and tailored therapy. Long-term surveillance remains essential, as 12% of CUPs reveal primaries during follow-up.